Aquatic Organisms in Response to Salinity Stress: Ecological Impacts, Adaptive Mechanisms, and Resilience Strategies - Tariq Dildar; Wenxiao Cui; Mhd Ikhwanuddin; Hongyu Ma (Biology)
Salinity stress presents a major ecological challenge for aquatic organisms, particularly in environments where salinity levels fluctuate. These fluctuations are becoming more pronounced due to climate change, further destabilizing aquatic ecosystems. Understanding how organisms adapt to such variability is essential for biodiversity conservation and the sustainable management of aquatic resources. This review examines the physiological, molecular, and behavioral adaptations that enable aquatic organisms to survive and thrive under salinity stress. Specifically, it explores mechanisms of osmotic regulation, ion transport, and oxidative stress responses, highlighting key signaling pathways—such as AMP-activated protein kinase (AMPK), Phosphatidylinositol 3-kinase–protein kinase (PI3K-AKT), Mitogen-activated protein kinase (MAPK), and the Hippo pathway—that facilitate these adaptive processes. The review also emphasizes the genetic and epigenetic modifications that contribute to resilience, underscoring the importance of genetic diversity for species survival in fluctuating salinity conditions. Furthermore, the interactions between host organisms and their microbiomes are discussed as critical factors influencing resilience. The review addresses the impact of salinity fluctuations on species distribution and biodiversity, with a focus on the implications of climate change for aquatic ecosystems. Finally, strategies for mitigating salinity stress, such as nutritional interventions and the development of salinity-resistant varieties, are explored, particularly in aquaculture. Overall, this review consolidates current knowledge on organismal adaptations, molecular mechanisms, and environmental challenges, offering valuable insights for ecological research and aquaculture practices in the face of climate change.